Does size matter? - Dahlqvist,Erik (2018)
Since the middle of the nineties, the amount of Regional Trade Agreements has risen sharply. This have created more opportunities for countries to join world trading and be more connected to the rest of the world. However, each trade agreement is unique and it is therefore interesting to evaluate if there are factors that are more important than others. This paper will be looking at combined GDP and population for the agreement, as well as GDP per capita and number of countries in the agreement. What level of integration the agreement experiences can also play an important role, therefore there is a distinction between Free trade agreements (FTAs) and Custom unions. A dataset of 75 low to middle income countries were assembled and the bilateral trade between them, as well as data for the trade agreements they are a part of. The gravity model was then applied with variables for the before mentioned factors. The results were that combined GDP have a small, but positive effect on bilateral trade between member countries, and that the number of countries have a negative effect for both FTAs and customs unions. This suggest that a trade agreement between few, more developed countries is beneficial.
Keywords: Trade; Regional trade agreements; Gravity model